2018
DOI: 10.7150/ijbs.28249
|View full text |Cite
|
Sign up to set email alerts
|

Seven Genes Based Novel Signature Predicts Clinical Outcome and Platinum Sensitivity of High Grade IIIc Serous Ovarian Carcinoma

Abstract: Background: As a major subtype of ovarian cancer, high grade FIGO stage IIIc serous ovarian carcinoma (HG3cSOC), has various prognosis due to genetic heterogeneity.Methods: The transcriptome of 401 primary FIGO IIIc serous ovarian samples was screened, seven genes based prognostic model was developed. The prognostic valueof risk score in four different cohorts (TCGA-cohort, Poland-cohort, Japan-cohort and USA-cohort) was validated. The relationship between risk score and other clinical indicators were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Yu and his colleagues identified of differential AS genes by expression profiling in gliomas [25]. Novel signature (seven genes) indicated clinical reaction and platinum sensitivity of serous ovarian carcinoma [26]. Xie et al studied prognostic splicing signatures and revealed regulatory network in esophageal carcinoma [27].…”
Section: Discussionmentioning
confidence: 99%
“…Yu and his colleagues identified of differential AS genes by expression profiling in gliomas [25]. Novel signature (seven genes) indicated clinical reaction and platinum sensitivity of serous ovarian carcinoma [26]. Xie et al studied prognostic splicing signatures and revealed regulatory network in esophageal carcinoma [27].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple gene signatures have been developed to predict overall survival, recurrence, and platinum sensitivity in OC. Some gene signatures were also used to predict the overall survival outcome in SOC [14,35,36]. Liu et al developed a seven gene-based novel signature to predict clinical outcomes of High-Grade IIIc Serous Ovarian Carcinoma with an AUC of 0.715 in the TCGA cohort [35].…”
Section: Discussionmentioning
confidence: 99%
“…Some gene signatures were also used to predict the overall survival outcome in SOC [14,35,36]. Liu et al developed a seven gene-based novel signature to predict clinical outcomes of High-Grade IIIc Serous Ovarian Carcinoma with an AUC of 0.715 in the TCGA cohort [35]. A genomic rearrangement signature was constructed in High-Grade Serous Ovarian Cancer (HGSOC) with an AUC of 0.63 in the TCGA cohort [36].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al established a prognostic model based on seven genes. After systematic analysis, they indicated that the optimized seven-gene-based model can be used as a valuable marker of the response to platinum-based chemotherapy and a valuable and powerful tool for predicting the survival of FIGO IIIc serous ovarian cancer (Liu et al, 2018 ). Most of the studies mentioned above focused on the differences between platinum-resistant or -sensitive patients through comparison and excluded low-throughput experiments.…”
Section: Introductionmentioning
confidence: 99%